Strawberry notch homolog 2 is a novel inflammatory response factor predominantly but not exclusively expressed by astrocytes in the central nervous system. Issue 10 (22nd April 2015) - Grill, Magdalena; Syme, Taylor E.; Noçon, Aline L.; Lu, Andy Z. X.; Hancock, Dale; Rose‐John, Stefan; Campbell, Iain L.
<x xml:space="preserve">Abstract</x> Interleukin‐6 (IL‐6) participates in the host response to injury and infection in the central nervous system (CNS). We identified strawberry notch homolog 2 (Sbno2) as an IL‐6‐stimulated gene in murine astrocytes. Sbno2 is a mouse homolog of the sno gene in Drosophila but little is known about the regulation or function of the mammalian gene. Here we examined the regulation of the Sbno2 gene in astrocytes in vitro and in the murine CNS following systemic endotoxin administration. In murine and human cultured astrocytes, Sbno2 gene expression was significantly upregulated in a dose‐ and time‐dependent fashion by hyper‐IL‐6 (IL‐6 + soluble IL‐6 receptor). The level of Sbno2 mRNA was also upregulated significantly in murine astrocytes by other glycoprotein130 cytokine‐family members and the pro‐inflammatory cytokines interleukin‐1 beta and tumor necrosis factor alpha. These changes were reflected by corresponding alterations in the level of the SBNO2 protein. Inhibiting protein synthesis resulted in higher Sbno2 mRNA and did not abolish the upregulation of Sbno2 mRNA mediated by hyper‐IL‐6. Inhibition of transcription led to a rapid reduction in hyper‐IL‐6‐induced Sbno2 mRNA in astrocytes suggesting that the Sbno2 mRNA is quite unstable. Following intra‐peritoneal lipopolysaccharide injection in mice, Sbno2 mRNA levels in the brain were significantly increased. Cellular localization studies revealed that this increase in Sbno2 mRNA occurred predominantly in astrocytes and in the choroid plexus and in some microglia, endothelial cells, and neurons. These findings are consistent with SBNO2 functioning as an acute inflammatory response gene in astrocytes as well as other cells in the CNS. GLIA 2015;63:1738–1752